Pengembangan Komik Sains untuk Siswa Sekolah Dasar/Madrasah Ibtidaiyah Menuju Banjarmasin Siaga Banjir - Cahyadi, Ani; Ningsih, Murni; Islamy, M. Irfan (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Banjarmasin as a lowland city, many small, medium, and large rivers, the majority of swamp areas, would be interesting to be used as an object in education as a place to learn about the knowledge and cultures of the river that characterized by region. The right place is education, especially elementary school which is the most appropriate target in instilling awareness on early. World of education, learning will be interesting if the media are included to make students more excited in the learning process. Comics contained illustration of character, scene, and groove usually arranged as entertainment. in this research developed in the form of science comic based on disaster mitigation, that is flood disaster with hope to be as educative media of learning also as entertainment for student. This research uses model of ADDIE media product development. The research developing two comic entitled "Amang si Pembelajar" and "Belajar Siaga Banjir (BSB)" with good quality in terms of material with a score of 3.22 and excellent quality in terms of learning media with the final average of 3.3. Science comics based on flood mitigation is full color and in accordance with the needs of primary school